Repair of Tibial Plateau Fracture (Schatzker II). Issue 3 (July 2019) - Lowe, Dylan T.; Milone, Michael T.; Gonzalez, Leah J.; Egol, Kenneth A.
Abstract : Tibial plateau fracture is an injury commonly seen by those who treat trauma around the knee and/or sports-related injuries. In this video article, we present our protocol for surgical treatment of a tibial plateau fracture, which includes definitive fixation with use of a plate-and-screw construct, addressing of all associated soft-tissue injuries at the time of the surgical procedure, filling of any residual voids with bone cement, and early rehabilitation with weight-bearing beginning at 10 to 12 weeks postoperatively. The major steps of the procedure are (1) preoperative planning with digitally templated plates and screws, (2) patient positioning and setup, (3) anterolateral approach toward the proximal aspect of the tibia, (4) submeniscal arthrotomy, (5) booking open of the proximal aspect of the tibia at the fracture site, (6) tagging of the meniscus, (7) fracture reduction and placement of the Kirschner wire, (8) confirmation of reduction with C-arm image intensification, (9) internal fixation with a plate-and-screw construct, and (10) closure.